PENGEMBANGAN MEDIA KARTU KALIMAT MATERI PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA SISWA KELAS II SDN KASREMAN KANDANGAN - Bella Ayu Permata Sari; Damariswara, Rian; Mujiwati, Endang Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the results of observations during the learning process for class II students at SDN Kasreman, Kandangan District. Learning material on the use of capital letters and punctuation in Indonesian language learning has problems. First, the learning media used by the teacher for material on the use of capital letters and punctuation marks is only letter cards. Using letter card media, teachers have not directly involved students in practicing this media. Second, teaching and learning interactions between teachers and students are lacking.  The method used in this research is R&D (Research and Development) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this research were 26 class II students at SDN KASREMAN. The data collection techniques used were questionnaires and tests. Meanwhile, the data analysis technique uses quantitative analysis techniques which are explained using qualitative analysis. The results of this research are: (1) the validity of the sentence card media obtained a media validation result of 92.7% which was declared very valid, material validation obtained a score of 84% which was declared valid and learning device validation obtained a score of 93% which was declared very valid; (2) the sentence card media material using capital letters and punctuation was stated to be practical by obtaining results from teacher response questionnaires of 87.5%, student response questionnaires of 90% limited trials and 93.3% extensive trials; and (3) the sentence card media was declared effective after limited trials by providing posttest questions at 86.2% and extensive trials providing posttest questions obtained results of 90.5% so that the sentence card media could be said to be very effective without any improvements.